Building reversibility: executive design examples - Massimo Lauria (Agathón)
The article presents executive design examples carried out in recent years on the topic of building reversibility. It is an activity whose results have a double interpretive register. On the one hand, they allow dissemination and sharing of teaching practices related to the current disciplinary statute reconfigurations. On the other hand, they help us to explore how the transformations of the current scenario are reshaping cultural, technical and operational boundaries of the relationship between built environment transformation, plan, its teaching and the profile of the designers educated in the Architecture schools.